Peruvian Andean amphibians outside Natural Protected Areas: Threats and conservation status - Aguilar, César (2010)
We present an updated list of amphibians occurring in Peru, and for Andean amphibians (those which are found above 1000 m of altitude) IUCN categories, number of endemic species, threats and presence in SINANPE (National System of Protected Areas of Peru) are mentioned. 538 species of amphibian are recognized in Peru at 2010, 110 species were registered since 2003 to 2010, one species per month. Of those 110 species, 77 were Andean species and 64% of them occur outside SINANPE. A total of 235 Andean species are recognized, 80% are endemic to Peru and 58% of these endemic species are outside SINANPE. A total of 91 Andean species are in threatened and Near Threatened categories, and 53% of them occur outside SINANPE. Genera Telmatobius and Atelopus, as well as, families Centrolenidae and Strabomantidae occurring in Peru, show the highest percentage of Andean species categorized as threatened and Near Threatened by the IUCN. For 83 (36%) Andean peruvian amphibians, the main threat is habitat loss. Other threats are chytridiomycosis, habitat degradation and overexploitation, but they are present at lower percentages. We recommend the promotion of private conservation areas for Andean peruvian amphibians, which are in threatened categories, are endemics and occurs outside SINANPE.